Salary standardization ; Media credibility ; Sigaw ng Penpen [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Tackles government employees protest against SSL and an interview with Rep. Rodolfo Andaya, SSL author; media's credibility as a source of news focusing on SWS survey and Penpen with its pop music using purely contemporary Filipino neo-ethnic rock concept of music.
Salary standardization (11 min.) -- Media credibility (16 min.) -- Sigaw ng Penpen (17 min.)
VHS.
Keywords: Penpen (Singing group); Wages -- Philippines; Mass media surveys -- Philippines; Mass media -- Philippines; Popular music -- Philippines; Philippines -- Government employees -- Salaries, etc; Mass communication; Music; Labor relations